Skill Mismatch yang Dirasakan oleh Alumni Program Studi Diploma IV Akuntansi Politeknik Negeri Padang - Azalia, Annice; Sudiman, Josephine; Maryati, Ulfi (Akuntansi dan Manajemen, 2021)
Many previous studies found that there was dissatisfaction with graduate users with the competencies possessed by Accounting graduates. Importantly, Accounting graduates must prepare themselves for various competencies needed in the world of work. This purpose of this study is to examine whether there is a competency gap faced by the graduates of Accounting Department of the Padang State Polytechnic while performing their first job. This study uses a quantitative method. Sample selected purposively on the alumni of D-IV 4 Accounting at the Padang State Polytechnic with 54 respondents that had worked after graduation. The data analysis technique in this study used the sign test and the Mann-Whitney U test. The results show that there is a competency gap faced by alumni in the attributes of technical and IT skills except in presenting financial reports, planning and conducting audits, implementing internal controls, measuring company performance, using Office, accounting software and social media. There is also no difference found in competency level between graduates of 2019 and 2020.